Development of differential evolution based Power System Stabilizer (PSS) with HVDC in small signal stability analysis using MATLAB - Azizan, Mohd Syukur (2015)
Power system (PS) oscillation damping remains as one of the major concerns for secure and reliable operation of large PS network, and is of great presently interest to both industry and academia. This research presents the designing of Differential Evolution (DE) power system stabilizer (PSS) controller with High Voltage Direct Current (HVDC) to improve the small signal stability (SSS). The Power System Toolbox version 3 MATLAB based software is used as a tool to simulate the results. The results shown that the location of HVDC supplementary in the network contribute to the effectiveness in improving power system SSS if applied together with the PSS. The results show a significant improvement to the damping of the inter-area mode as well the local mode oscillation when the DEPSS incorporated into system together with HVDC which is approximated 5% improvement. Thus the time domain response also shown improve beyond 10%.